THE EFFECT OF PRICE TO BOOK VALUE AND CORPORATE SOCIAL RESPONSIBILITY ON ABNORMAL RETURNS - Shinta Amalia Sani; Nyimas Wardatul Afiqoh (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective: This study aims to examine the effect of Price Book Value (PBV) and Corporate Social Responsibility (CSR) on abnormal returns in LQ45 indexed companies on the Indonesia Stock Exchange during the 2022-2024 period. Method: The method used in this study is a quantitative approach with a purposive sampling technique, resulting in 35 companies as research samples. Data were analyzed using multiple linear regression with the help of SPSS. Results: The results show that Price Book Value (PBV) has a negative and significant effect on abnormal return. Meanwhile, Corporate Social Responsibility (CSR) does affect abnormal return. However, the results of the simultaneous test show that PBV and CSR have an effect on abnormal return. Novelty: The novelty of this study lies in its integrated analysis of market valuation metrics and sustainability disclosures during the volatile post-pandemic economic recovery period of 2022–2024. Unlike previous studies that often treat financial indicators and non-financial disclosures in isolation, this research provides fresh empirical evidence from Indonesia's most liquid capital market segment (LQ45), revealing the nuanced dynamics and shifting investor priorities where corporate social responsibility indicators interact simultaneously with valuation multiples to drive abnormal market returns.